Effects on Personal Factors Through Flipped Learning and Gamification as Combined Methodologies in Secondary Education - Segura-Robles, Adrián; Fuentes-Cabrera, Arturo; Parra-González, María Elena; López-Belmonte, Jesús (Frontiers in Psychology, 2020)
Purpose: This study aims to analyze the effects of a flipped and gamified program on the autonomy, competence, relation with others, satisfaction/enjoyment, intrinsic and extrinsic motivation and boredom of students of Physical Education. Method: The study used a control and experimental group to compare pretest and posttest data in both of them. Instruments used were the Basic Psychological Needs in Exercise Scale, Sport Motivation Scale and Sport Satisfaction Instrument, all of them validated in academic literature. Results: On one hand, data indicated that autonomy have been increased with the application of these teaching methodologies. On the other hand, students’ satisfaction, enjoyment, and intrinsic motivation have improved, based on the interaction with gamification and flipped learning. Finally, with all dimensions it seems that academic performance has been improved, although nor in a significative way. Discussion/Conclusion: Results of the study provide to educational researchers valuable information for a better understanding of how flipped learning and gamification influences in personal and performance of physical education students.